Type material housed in the Helminthological Collection of the Museo de La Plata, Buenos Aires, Argentina - Lunaschi, Lia I.; Álvarez, Victor Hugo Merlo; Damborenea, Cristina (Zootaxa, 2012)
A catalogue of type specimens of the Helminthological Collection of the División Zoología Invertebrados, of Museo deLa Plata (FCNyM-UNLP), Argentina, is presented. It includes Platyhelmithes, Nematoda, Nematomorpha and Acan-thocephala. The collection comprises type lots for 217 species: 90 nematodes, 50 digeneans, 28 Nematomorpha, 19 mono-geneans, 17 turbellarians, 8 cestodes and 5 acanthocephalans. Specific names are listed systematically, followed by type host, type locality, specimens, collection number and bibliographic reference.